Selective sodium-dependent glucose transporter 1 inhibitors block glucose absorption and impair glucose-dependent insulinotropic peptide release - Dobbins, Robert L.; Greenway, Frank L.; Chen, Lihong; Liu, Yaping; Breed, Sharon L.; Andrews, Susan M.; Wald, Jeffrey A.; Walker, Ann; Smith, Chari D. (American journal of physiology: Gastrointestinal and liver physiology, 2015)
GSK-1614235 and KGA-2727 are potent, selective inhibitors of the SGLT1 sodium-dependent glucose transporter. Nonclinical (KGA-2727) and clinical (GSK-1614235) trials assessed translation of SGLT1 inhibitor effects from rats to normal human physiology. In rats, KGA-2727 (0.1 mg/kg) or vehicle was given before oral administration of 3- O-methyl-α-d-glucopyranose (3- O-methylglucose, 3-OMG) containing 3-[ 3 H]OMG tracer. Tracer absorption and distribution were assessed from plasma, urine, and fecal samples. SGLT1 inhibition reduced urine 3-OMG recovery and increased fecal excretion. SGLT1 inhibitor effects on plasma glucose, insulin, gastric inhibitory peptide (GIP), and glucagon-like peptide-1 (GLP-1) concentrations were also measured during a standard meal. Incremental glucose, insulin, and GIP concentrations were decreased, indicating downregulation of β-cell and K cell secretion. Minimal effects were observed in the secretion of the L cell product, GLP-1. With the use of a three-way, crossover design, 12 healthy human subjects received placebo or 20 mg GSK-1614235 immediately before or after a meal. Five minutes into the meal, 3-OMG was ingested. Postmeal dosing had little impact, yet premeal dosing delayed and reduced 3-OMG absorption, with an AUC 0–10 of 231 ± 31 vs. 446 ± 31 μg·h −1 ·ml −1 , for placebo. Recovery of tracer in urine was 1.2 ± 0.7 g for premeal dosing and 2.2 ± 0.1 g for placebo. Incremental concentrations of insulin, C-peptide, and GIP were reduced for 2 h with premeal GSK-1614235. Total GLP-1 concentrations were significantly increased, and a trend for increased peptide YY (PYY) was noted. SGLT1 inhibitors block intestinal glucose absorption and reduce GIP secretion in rats and humans, suggesting SGLT1 glucose transport is critical for GIP release. Conversely, GLP-1 and PYY secretion are enhanced by SGLT1 inhibition in humans.